Complex antigen presentation pathway for an HLA-A*0201-restricted epitope from Chikungunya 6K protein. - Elena Lorente; Alejandro Barriga; Juan García-Arriaza; François A Lemonnier; Mariano Esteban; Daniel López (Public Library of Science (PLoS), 2017)
The adaptive cytotoxic T lymphocyte (CTL)-mediated immune response is critical for clearance of many viral infections. These CTL recognize naturally processed short viral antigenic peptides bound to human leukocyte antigen (HLA) class I molecules on the surface of infected cells. This specific recognition allows the killing of virus-infected cells. The T cell immune T cell response to Chikungunya virus (CHIKV), a mosquito-borne Alphavirus of the Togaviridae family responsible for severe musculoskeletal disorders, has not been fully defined; nonetheless, the importance of HLA class I-restricted immune response in this virus has been hypothesized.By infection of HLA-A*0201-transgenic mice with a recombinant vaccinia virus that encodes the CHIKV structural polyprotein (rVACV-CHIKV), we identified the first human T cell epitopes from CHIKV. These three novel 6K transmembrane protein-derived epitopes are presented by the common HLA class I molecule, HLA-A*0201. One of these epitopes is processed and presented via a complex pathway that involves proteases from different subcellular locations. Specific chemical inhibitors blocked these events in rVACV-CHIKV-infected cells.Our data have implications not only for the identification of novel Alphavirus and Togaviridae antiviral CTL responses, but also for analyzing presentation of antigen from viruses of different families and orders that use host proteinases to generate their mature envelope proteins.